Exploring the role of gut microbiota in autoimmune thyroid disorders: a systematic review and meta-analysis - Alkader, Dania Akeil Abed; Asadi, Naweedullah; Solangi, Uzma; Singh, Ransherjit; Rasuli, Sayed Farhad; Farooq, Muhammad Jawad; Raheela, F. N. U.; Waseem, Radeyah; Gilani, Syed Mujahid; Abbas, Kiran; Ahmed, Moiz; Tanoh, Desmond Boakye; et al. (Frontiers in Endocrinology, 2023)
Background: Autoimmune thyroid diseases (AITDs) are characterized by unique immune responses against thyroid antigens and persist over time. The most common types of AITDs are Graves' disease (GD) and Hashimoto's thyroiditis (HT). There is mounting evidence that changes in the microbiota may play a role in the onset and development of AITDs. Objective: The purpose of this comprehensive literature study was to answer the following query: Is there a difference in microbiota in those who have AITDs? Methods: According to the standards set out by the PRISMA statement, 16 studies met the requirements for inclusion after being screened for eligibility. Results: The Simpson index was the only diversity measure shown to be considerably lower in patients with GD compared to healthy participants, whereas all other indices were found to be significantly greater in patients with HT. The latter group, however, showed a greater relative abundance of Bacteroidetes and Actinobacteria at the phylum level, and consequently of Prevotella and Bifidobacterium at the genus level. The strongest positive and negative relationships were seen for thyroid peroxidase antibodies and bacterial load. Conclusion: Overall, both GD and HT patients showed significant changes in the gut microbiota's diversity and composition.